Market Potential and the Location of Japanese Investment in the European Union - Head, Keith; Mayer, Thierry (The Review of Economics and Statistics, 2004)
This paper develops a theoretical model of location choice under imperfect competition to formalize the notion that firms prefer to locate “where the markets are.” The profitability of a location depends on a term that weights demand in all locations by accessibility. Using a sample of Japanese firms' choices of regions within European countries, we compare the theoretically derived measure of market potential with the standard form used by geographers. Our results show that market potential matters for location choice but cannot account entirely for the tendency of firms in the same industry to agglomerate.